Pelatihan Kerajinan Mendaur Ulang Sampah dalam Meningkatkan Pendapatan Organisasi Aisiyah Kota Medan - Winarti Winarti; Muhammad Shareza Hafiz; Sri Listiana Izar (CERED Indonesia Publishing, 2020)
Garbage is one of the problems that occur in our daily lives. Every morning we see garbage piled up in every alley of houses, which then ends up in the Final Disposal Site (TPA). The more garbage, the higher the level of environmental pollution around us. We don't realize it today, but we will feel God's curse someday if trash doesn't get an answer right away. Housewives, including Aisyiyah, are one of the Muhammadiyah organizations that was born in the community who always produce household waste every day. It was they who witnessed how these rubbish experienced travel from supermarkets or traditional markets, to homes and kitchens, then trash cans, until they ended up in landfills in the aisles of the house or in front of the house for city cleaners to take. This research method is by giving training to Aisiyah's mothers on how to utilize waste so that it becomes an efficient product. So that these wastes are good and do not damage the environment, then a brilliant solution is offered. Trash is